4-Hydrazino-1-methylpyrazolo[3,4-d]pyrimidine. - Dolzhenko, Anton; Pastorin, G.; Dolzhenko, A.; Tan, G.; Koh, L. (Blackwell Munksgaard, 2009)
The title compound, C6H8N6, crystallizes as an NH...N hydrogen-bond-linked dimer of two almost identical molecules in the asymmetric unit. Both of the molecules are almost planar (rms deviations of 0.0186 and 0.0296 Å in the two molecules) and their hydrazino groups are turned towards the pyrazole rings. The dimers are arranged into chains via intermolecular NH...N hydrogen bonds between the hydrazino groups and the N atoms of the pyrimidine rings of both types of the molecules, linking the molecules into a C(7) graph-set motif along [100]. The methyl groups and the N atoms of the pyrazole rings form weak CH...N hydrogen bonds, which connect chains of the dimers in a C(4) motif parallel to [100].